2016
DOI: 10.5603/kp.a2016.0004
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of red cell distribution width and other red cell parameters in patients with chronic heart failure during two years of follow-up

Abstract: A b s t r a c tBackground: Studies published during the last decade seem to indicate red blood cell parameters as inexpensive, rapidly available, and simple tools for the assessment of prognosis in patients with chronic heart failure (CHF). Aim:To evaluate the prognostic value of red cell parameters determined in a routine blood count in patients with CHF. Methods:The study group included 165 patients with the New York Heart Association (NYHA) class II-IV CHF hospitalised in the 2 nd Department of Cardiology i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…The authors found that RDW exhibited the strongest association with cardiovascular death or HF hospitalization (adjusted HR 1.17 per 1-SD increase, 95% CI: 1.10–1.25, p < 0.001) among 36 laboratory parameters in a cohort of 2679 symptomatic chronic HF patients from the North American CHARM (Candesartan in Heart Failure: Assessment of Reduction in Mortality and Morbidity) program. Similar were the findings in the Study of Anemia in a Heart Failure Population (STAMINA-HFP) [ 18 , 34 ], as well as in patients post myocardial infarction (MI) [ 35 ]. In this regard, it has been proposed that RDW may be a better predictor of outcomes in HF patients than several echocardiographic parameters [ 36 ].…”
Section: Rdw Change In Heart Failuresupporting
confidence: 77%
“…The authors found that RDW exhibited the strongest association with cardiovascular death or HF hospitalization (adjusted HR 1.17 per 1-SD increase, 95% CI: 1.10–1.25, p < 0.001) among 36 laboratory parameters in a cohort of 2679 symptomatic chronic HF patients from the North American CHARM (Candesartan in Heart Failure: Assessment of Reduction in Mortality and Morbidity) program. Similar were the findings in the Study of Anemia in a Heart Failure Population (STAMINA-HFP) [ 18 , 34 ], as well as in patients post myocardial infarction (MI) [ 35 ]. In this regard, it has been proposed that RDW may be a better predictor of outcomes in HF patients than several echocardiographic parameters [ 36 ].…”
Section: Rdw Change In Heart Failuresupporting
confidence: 77%
“…Recently, MCV has been associated with mortality in many clinical settings [ 13 ]. Wolowiec et al [ 5 ] found that there was no statistically significant relationship between MCV and the prognosis of patients with heart failure with 1-year follow-up. In our study, no mortality-predicting role can be assumed for MCV in heart failure patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mean corpuscular hemoglobin represents the average amount of Hb in RBCs, and Hb is essential for the distribution and delivery of oxygen to the tissues [ 24 ]. Following a study by Wolowiec et al [ 5 ] that showed MCH was not a prognostic factor in heart failure patients, the current project failed to determine the MCH as a 1-year mortality predictor. Although it possesses an acceptable significant sensitivity in ROC analysis, in the multivariate model, with the effect of other co-factors, the prognostic utility was alleviated, and it cannot be supposed as a predictor.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding to the prognostic value of RDW in patients with HF, it has been concluded that RDW independently predicts one-year mortality in acute HF patients, as well as in patients with chronic HF [14,15]. High RDW values also predict poor long-term outcome regardless of anaemia status in HF patients [16].…”
Section: Discussionmentioning
confidence: 99%